(untitled) (LEARNing Landscapes, 2016)
Having been nurtured in the counting culture in Nigeria, my discovery of qualitative research methodology was as novel and subversive as using my left hand, which is considered a taboo in many Nigerian homes. This paper relates my initial attempt to deploy a qualitative methodology, especially art as a research tool, in investigating why Nigerian senior secondary school students and teachers hated Oral English. That study provided a canvas for the exhibition of art in my inquiry.